2006
DOI: 10.1002/elps.200600261
|View full text |Cite
|
Sign up to set email alerts
|

Chiral microemulsion electrokinetic chromatography: Effect of cosurfactant identity on enantioselectivity, methylene selectivity, resolution, and other chromatographic figures of merit

Abstract: The effect of cosurfactant identity on microemulsion size, elution range, retention factor, enantioselectivity, methylene selectivity, efficiency, and resolution in chiral microemulsion formulations was examined. The chiral surfactant dodecoxycarbonylvaline was used in conjunction with the cosurfactants 1-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, cyclopentanol, and cyclohexanol. The millimolar concentration of cosurfactant was held constant regardless of identity. Ethyl acetate was incorporated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In addition to the use of a chiral surfactant [17][18][19][20][21][22] or a chiral cosurfactant 23 as the enantioselective element within the microemulsion droplets in MEEKC, the present study was demonstrated for a novel chiral-MEEKC system employing optically active (S)-(+)-2-octanol as a chiral oil for effecting the enantioseparation of basic drugs in MEEKC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the use of a chiral surfactant [17][18][19][20][21][22] or a chiral cosurfactant 23 as the enantioselective element within the microemulsion droplets in MEEKC, the present study was demonstrated for a novel chiral-MEEKC system employing optically active (S)-(+)-2-octanol as a chiral oil for effecting the enantioseparation of basic drugs in MEEKC.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,23 In addition, it is also recognized that organic modifiers can have an effect on the electroosmotic flow (EOF), the viscosity, the dielectric constant, the conductivity of the background electrolyte, and the solubility of the analytes. 27 Consequently, the effect of the 1-butanol concentration (4.4 to 8.8% (w/w)) on the enantioseparation of (±)-norephedrine was studied; and the obtained results can be seen in Fig.…”
Section: Influence Of the Cosurfactantmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, racemic 2-hexanol was tested as a cosurfactant and found to greatly improve efficiency over the previously used 1-butanol. Another DDCV study compared the effects of seven different achiral cosurfactants (primary, secondary, and cyclic alcohols at equimolar concentrations) on the enantioseparation of six pairs of pharmaceutical enantiomers [67]. The main trends identified were: higher enantioselectivity with cyclic and short chain primary alcohols (1-butanol and cyclopentanol), lower enantioselectivity with longer chain primary alcohols, largest overall efficiency with 1-hexanol, and largest overall resolution with 1-butanol.…”
Section: Microemulsionsmentioning
confidence: 99%
“…The first such publication described chiral selectivity achieved by using an aggregate system consisting of an achiral surfactant, an achiral cosurfactant, and a chiral oil (dibutyl tartrate) [49]. Several investigations in chiral MEEKC have been performed by our group with the surfactant dodecoxycarbonylvaline (DDCV) serving as the only chiral selectand in the PSP formulation and have focused on variations of surfactant concentration [50], buffer identity [50], oil identity [51], temperature [52], and cosurfactant identity [53]. There has been one report where the chiral surfactant (polysodium N-undecenoyl-D-valinate, poly-D-SUV) was utilized in two ways for chiral EKC: (i) cosurfactant and oil phases were added to poly-D-SUV micelles to form a microemulsion solution and (ii) the surfactant was polymerized under microemulsion conditions and subsequently employed under nonmicroemulsion conditions as the material was rotavaporized and freeze-dried prior to dissolution in buffer [54].…”
Section: Introductionmentioning
confidence: 99%